On Migration Diasporization - Transculturality - Transmediality - Sieber, Cornelia (Georg Olms Verlag, 2020)
This volume is based on the section "Transnationalities - Transidentities - Hybridities - Diasporization", organized by the Ibero-American and Francophone Research Centres of the University of Leipzig as part of the First Annual Conference of the Centre for Area Studies at the University of Leipzig. By now, already a decade has passed since our conference section took place and it is due to various circumstances that this volume has not been published earlier. It carries along, in some sense, its own migration trace. Nevertheless, the questions examined in the contributions have reached even more relevance since then in both, the Old World and the New, due to the various political, social, economic and ecological crisis around the globe that have led to the increased arrival of refugees to Europe and the harsh discussion about a concrete or "intelligent" wall to shield the USA from Latin American migrants, among others. Today, there is an urgent political and social need for concepts of living together in much more heterogeneous and much less familiar societies. The questions, notions and cases explored in the nine contributions that comprise this publication focus on this emergency.